Deformation behavior of additive manufactured 316 L stainless steel using in situ neutron diffraction - Zhiping Chen; Zhenjun Jiang; Fuzhu Wang; Dandan Zhao; Xiaodong Zhang; Chen Wang; Jianfei Hao; Mengmeng Tong; Bin Chen; Hao Jie Kong; Bingbing Wan; Runxia Li; et al. (Scientific Reports)
Abstract Manufacturing of metallic components using additive manufacturing technique is of great interest for the industrial applications. Here, the mechanical and microstructural responses of a 316 L stainless steel (316LSS) built by selective laser melting (SLM) with XOY and XOZ directions were revealed by performing in situ neutron diffraction tensile tests. The tensile strength of the XOY-printed samples reaches 700 MPa, while the tensile strength of the XOZ-printed samples is less than 600 MPa. The as-printed 316LSS exhibits anisotropy in tensile property due to the formation of different fractions of nano-sized dimples, twin boundaries, diffraction peak and lattice constants during tensile tests at room temperature. Therefore, choosing right printing direction plays a vital role in forming of metal parts using SLM for further application.